Kelayakan Media Ensiklopedia Pada Submateri Tingkat Keanekaragaman Hayati Dari Hasil Inventarisasi Tumbuhan Araceae Di Hutan Lindung Gunung Raya Kabupaten Sambas - Sapriani, Sri; ., Syamswisna; ., Titin (CV.ITTC INDONESIA, 2024)
On level of biodiversity is the Araceae plant species found in the Gunung Raya protected forest, Sambas Regency. Published in the encyclopedia media, it contains shrt descriptions that are arranged systematically, so that they are easy to understand and can be used i schls that are hampered by LCD. This research airns t determine the suitability of encyclopedia media for the level of biodiversity from the results of a iventory of Araceae plants in the Gunung Raya Protected Forest, Sambas Regency. This research was carried out in two stages, namely the first stage was an inventory of Araceae plants using quantitative descriptive methods in the Gunung Raya Protected Forest, Temajuk village, Paloh district, Sambas Regency and the second stage was making encyclopedia media from the results of the inventory of Araceae plants using the research and Development (R&D) method. Developed only to the validation stage. The encyclopedia media was validated by 5 validators cosisting of 2 lecturers and Biology teachers. The validation results were analyzed usig the CVR Lawshe formula, a CVI value of 0,99 was obtained which was classified as valid using and 14 criteria. This, it can be concluded that the encyclopedia media created as an implementation of the results of the inventory of Araceae plants in the Gunung Raya Protected Forest, Sambas Regency is suitable for use as a learning media at the sub-material level of biodiversity.